Fatigue Damage Analysis of an Asphalt Mixture Based on Pseudostiffness - Wang, X.R.; Yin, B.Y.; Luo W.B. (Проблемы прочности, 2018)
The fatigue damage characteristics of an asphalt mixture were analyzed, a new fatigue damage model was constructed based on the Schapery pseudovariable theory and continuum damage mechanics. According to the Schapery theory and the generalized elastic-viscoelastic correspondence principle, the experimental stress–strain curves of the asphalt mixture are transformed into the stress vs. pseudostrain curves. The relation between stress and pseudostrain is shown to be linear, which eliminates the viscoelastic hysteresis effect of the asphalt mixture and its time dependence.